Design and Development of Stabiliser for Electric Unicycle - Azizi, M.A.; Ashaari, R.; As’arry, A.; Hafiz, M.R. (Journal of the Society of Automotive Engineers Malaysia, 2020)
This paper presents the research on design improvement of a self-balanced electric unicycle model which is available in the market. The improvement work is focused on the stability and the ease-of-use of the electric unicycle. The selected method for improvement is the automatic support wheels. In terms of stability, the additional two small wheels at both sides of the unicycle increase the contact area perpendicular to the unicycle motion and thus reduce the tendency of toppling to the lateral direction. The additional wheels can be expanded and retracted by using a control system where it is suggested that the wheels fold out at riding speed lower than 10km/h and fold in at riding speed higher than 10km/h. These retractable wheels overcome the difficulty of travel initiation and stopping of the original unicycle. The experiment shows that by using the prototype, the users experience better stability when using the unicycle with retractable wheels compare to when using the original unicycle.